Survival Outcomes Following Chemotherapy for High-Grade Central Nervous System Tumors in Adolescents and Young Adults: An Exploration of Variations According to Ethnicity and Deprivation - Sciberras, Peter; Cromie, Kirsten; Radford, Anna; Glaser, Adam; Feltbower, Richard G; Hughes, Nicola (Journal of adolescent and young adult oncology, 2025)
Adolescents and young adults (AYA) are a unique subgroup of patients who experience cancer at the interface between pediatric and adult oncology services. Central nervous system (CNS) tumors are the leading cause of cancer-related morbidity and mortality in this group. Socioeconomic status and ethnicity are known to impact CNS tumor survival in patients of all ages. Studies reporting AYA CNS survival outcomes by ethnicity and area-based deprivation, however, are lacking in the United Kingdom (UK). Using cancer registration data for 351 patients (12-29 years) who received systemic chemotherapy for a high-grade malignant CNS tumor in England between April 2014 and December 2018, we quantified differences in survival at 1, 2, and 3 years post-diagnosis by ethnicity and area-based socioeconomic status. Lower survival estimates were seen for non-White ethnicity and lower socioeconomic groups. Three-year survival was 64.4% (95% CI 58.3-69.9) for White patients but 46.6% (95% CI 29.9-61.7) for non-Whites and 64.0% (95% confidence interval [CI] 49.0-75.7) and 62.9% (95% CI 50.7-72.8) in those from the two least deprived fifths compared to 50.2% (95% CI 36.1-62.7) and 56.1% (95% CI 42.4-67.7) in the two most deprived groups. Our study is the first to show the existence of health disparities in AYA treated with chemotherapy for a primary CNS tumor in England, where patients from ethnic minorities and deprived areas had worse survival rates than their White and socioeconomically advantaged counterparts. These findings call for further research into the underlying reasons behind survival differences between sociodemographic groups to improve survivorship outcomes.